Geographical Indication and Rural Sustainable Development: A Bibliometric Analysis - Sanjay Singh; Nisha Bharti (Australasian Accounting, Business and Finance Journal, 2023)
Geographical Indications (G.I.s) mean a particular product belonging to a specific Geographical Environment, having a specific traditional knowledge which separates it from similar looking products. Certification is beneficial to both the producer as it can ensure him a premium price and the consumer as it generates the willingness to pay higher on quality assurance.GI also facilitates rural sustainable development as its uniqueness generates conservation of the resources in the concerned community. Bibliometric analysis is the scientific analysis of all the academic work done pertaining to a certain topic under study. It streamlines all the work done in a specific field and is also helpful in highlighting the areas where to focus for research. The main objective of this paper is to study the trend of development of the topic through the analysis of the entire academic work done. Data for the period from 2001 to 2021 was collected from web of science database and analyzed by using R package and VOS viewer software. Overall, 194 research papers were shortlisted. GI certification prevents commercial fraud, it ensures Bio-diversity conservation. Academic contribution has been maximum in the year 2019. Most relevant sources were Sustainability, British food journal. Among the most relevant keywords, frequency of words like Geographical Indications, quality, terroir, food, governance, certification, etc were on the higher side. Europe and USA dominate in certifications and contributions to GI Tagging followed by some developing countries like India, Mexico, Brazil. This study holds great relevance to people from all dimensions of life. There is a need to increase research in this area. The study will suggest several new dimensions to research which will be very much beneficial for the academicians, policy makers and particularly the rural community.
Keywords: Geographical Indications; Bibliometric analysis; Premium price; Rural sustainable development